Complex ultrasonography in the assessment of intrarenal hemodynamic impairments in patients with portal hypertension - L. V. Donova; M. S. Novruzbekov; V. E. Syutkin (Трансплантология (Москва), 2021)
Rationale. Hepatorenal syndrome is a threatening complication in patients with liver cirrhosis and portal hypertension. The occurrence of renal dysfunction associated with hepatorenal syndrome manifestations significantly affects the condition severity, the disease duration, and the survival time during the waiting period for liver transplantation.The study purpose was to investigate the potential of a complex ultrasonography examination in the assessment of intrarenal hemodynamic impairments in patients with various diffuse liver diseases.Material and methods. The ultrasound examination results of 167 patients were analyzed. The 1st group included 28 patients with confirmed diffuse liver diseases of viral etiology who did not have signs of cirrhosis formation, the 2nd group included 139 patients with liver cirrhosis due to diffuse liver diseases of various etiologies, and the 3-rd group included 137 patients who had previously been in the 2nd group in whom orthotopic liver transplantation was performed.Results. The study revealed a statistically significant increase in the incidence of secondary hemodynamic impairments in kidney function in patients with liver cirrhosis and no relationship of their severity and incidence to the disease etiology, and also to such markers of the portal hypertension severity as splenomegaly, ascites, and portal vein thrombosis.Conclusions. The resistive index measured on the renal arterial branches by Doppler ultrasound, has a certain predictive value in relation to hepatorenal syndrome in patients with liver cirrhosis of various origins. This also makes it possible to timely identify a group of patients at a high risk of developing severe renal dysfunction and to assess the efficacy of the treatment that has been given.